Review on National Electronic Identification System - Al-Nidawi W.J.A.; Maan M.A.; Othman M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Authentication; E- services; E-government services; E-governments; Electronic id; NeID; Government data processing